KARAKTER KEPEMIMPINAN GENERASI MUDA INDONESIA DALAM MASYARAKAT 5.0 - Dadi, Kanisius Komsiah (PERDIKKATI (Perkumpulan Pendidikan Keagamaan Katolik Indonesia), 2024)
This article explores the need for the Indonesian youth to develop authentic inner leadership characteristics that can guide them in navigating the unpredictable and challenging future. The author observes that the current technological advancements that have led to the emergence of an intelligent society focused on enhancing human dignity quality necessitate the development of strong leadership skills among the youth, who are society's present and future leaders 5.0. This article highlights six potential leadership traits: An awareness of technological progress, creativity and innovation, openness to diversity, respect for teamwork and collaboration, enthusiasm for learning and new knowledge, and an appreciation of the importance of ethics and integrity. The author used a qualitative research method and collected data from high school students in Java and Sumatra Islands of Indonesia using Google Forms. The study reveals that attaining effective leadership in the Society 5.0 era requires the Indonesian young generation to cultivate three essential life skills, including independent learning experiences, building global networks, and maintaining a continuous learning process. Practical leadership skills will help them navigate these challenges and emerge as successful leaders in the Society 5.0 era. In conclusion, the article highlights the importance of cultivating authentic inner leadership skills among the Indonesian youth to prepare them for future challenges. The traits identified in the study, including creativity, teamwork, and collaboration, are essential in ensuring that the young generation becomes influential leaders in the Society 5.0 era.